Effect of denosumab versus zoledronic acid in preventing skeletal-related events in patients with bone metastases by baseline characteristics. (January 2016) - Lipton, A.; Fizazi, K.; Stopeck, A.T.; Henry, D.H.; Smith, M.R.; Shore, N.; Martin, M.; Vadhan-Raj, S.; Brown, J.E.; Richardson, G.E.; Saad, F.; Yardley, D.A.; et al.
Abstract: Background: Analyses of phase III trials showed that denosumab was superior to zoledronic acid (ZA) in preventing skeletal-related events (SREs) irrespective of age, history of SREs, or baseline pain status. This analysis assessed the risk of SREs across additional baseline characteristics. Patients and Methods: Patients (N = 5543) from three phase III trials who had breast cancer, prostate cancer, or other solid tumours and one or more bone metastasis were included. Superiority of denosumab versus ZA in reducing risk of first SRE and first and subsequent SREs was assessed in subgroups defined by the Eastern Cooperative Oncology Group performance status (ECOG PS), bone metastasis location, bone metastasis number, visceral metastasis presence/absence, and urinary N-telopeptide (uNTx) level using Cox proportional hazards and Anderson–Gill models. Subgroups except bone metastasis location were also assessed for each solid tumour type. Results: Compared with ZA, denosumab significantly reduced the risk of first SRE across all subgroups (hazard ratio [HR] ranges: ECOG PS, 0.79–0.84; bone metastasis location, 0.78–0.83; bone metastasis number, 0.78–0.84; visceral metastasis presence/absence, 0.80–0.82; uNTx level, 0.73–0.86) and reduced the risk of first and subsequent SREs in all subgroups (HR ranges: ECOG PS, 0.76–0.83; bone metastasis location, 0.78–0.84; bone metastasis number, 0.79–0.81; visceral metastasis presence/absence, 0.79–0.81; uNTx level, 0.74–0.83). Similar results were observed in subgroups across tumour types. Conclusion: Denosumab was superior to ZA in preventing SREs in patients with bone metastases from advanced cancer, regardless of ECOG PS, bone metastasis number, baseline visceral metastasis presence/absence, and uNTx level. Highlights: Denosumab reduced the risk of first skeletal-related event (SRE) in all subgroups. Denosumab reduced the risk of first and subsequent SREs in all subgroups. The effect of denosumab on SRE risk was similar in subgroups across tumour types.